Local Governments as Nodes for Greenhouse Gas Abatement: Climate Change Governance in Multi- Level Frameworks - Franzén, Magnus (European Journal of Sustainable Development, 2013)
This research concentrates on the governance aspects of sustainability, and moreparticularly how local governments can work asnodes in a wider system of governance.The question at the center of the study is: how do cities address climate change mitigationand how do their actions relate to other levels of governance? The study takes a mixedqualitative-quantitative approach based on a multi-level theoretical framework to addressthe issue. The study concentrates on a smallnumber of cases and the material used isfound in official documents and semi-structured interviews with key individuals in thelocal governments. The results of the study show that the cities investigated do takeaction to mitigate climate change; however,their actions are heavily dependent on otherlevels of governance, i.e. regional or national, or other actors. This dependence,nonetheless, seems to be reciprocal. Thus, cities can constitute nodes or hubs in thegovernance of climate change mitigation,working simultaneously as actors ofimplementation and channelizing local knowledge and input.